The lost letters to the Twelve Prophets imagining the Minor Prophets' world - Goldingay, John (Grand Rapids Zondervan, 2022)
"Written as a series of imaginary letters to the Minor Prophets, The Lost Letters to the Twelve Prophets by renowned Old Testament scholar John Goldingay uncovers the issues Hosea, Micah, Zechariah, and others were responding to in their writings and unlocks the significance of these books for today's Christians"--
Includes index
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Miscellanea